Reflorestamento e recuperação de atributos químicos e físicos do solo - Rocha, José Henrique Tertulino; Santos, Alessandro José Marques; Diogo, Fernanda Asti [UNESP]; Backes, Clarice; De Melo, Augusto Gabriel Claro; Borelli, Karla; De Oliveira Godinho, Tiago (FapUNIFESP (SciELO), 2015)
The objective with this study was to evaluate the influence of reforestation with native species from seasonal semideciduous forest, eucalyptus plantation, and pasture in the soil chemical and physical properties of degraded areas. Five sites were selected in the watershed of the Aguapeí River in the Garça city, Sao Paulo state: two reforestation areas with native species, with four and nine years old; a reforestation area with eucalyptus plantation, a pasture area, and a forest fragment used as control. The forest fragment presented the lowest exangeable bases and the highest levels of P, SOC and CEC; it also showed the lowest penetration resistance, and the largest diameter and aggregate stability. The chemical and physical soil attributes of the reforestation areas differed from those of the forest fragment (control), showing that the recovery period was not sufficient to restore these attributes. However, the 9-year-old reforestation area presented significant improvement of these soil attributes, tending to approach those of the control area.
Reforestation and recovery of soil chemical and physical attributes
Keywords: Ecological indicators; Forest restoration; Soil quality